Turkish Children in Germany Learning Grammatical Categories in Turkish as a Mother Tongue - Kyuchukov, Hristo; Кючуков, Хрісто; Giray, Bariş; Гірай, Баріш (My University, 2018)
The paper presents and discusses findings from a recent empirical study involving 40 Turkish children aged between 4 and 6 years attending two kindergartens in Berlin in the districts of Wedding and Neukölln. They were tested for their knowledge and comprehension of different grammatical categories in Turkish. Children from Wedding were found to be much better in their knowledge of the grammatical categories in their mother tongue. The differences are statistically significant F (1.32) = 6.6258, p = 0.01488 (p< 0.05). The children from the kindergarten in Neukölln demonstrated lower results in Turkish grammar comprehension and thus their achieved literacy in L1.У статті йдеться про результати останнього дослідження із залученням 40 турецьких дітей віком від 4 до 6 років, які відвідують два дитячі садочки в Берліні в районах Веддинг та Нойкьольн. Дітей тестували щодо їхнього знання та розуміння різних граматичних категорій турецької мови. Як з’ясувалося, досліджувані з району Веддинг набагато краще знали граматичні категорії рідної мови. Відмінності були статистично значущими F (1.32) = 6.6258, p = 0.01488 (p< 0.05). На противагу, діти із садочку району Нойкьольн продемонстрували гірші результати розуміння граматики турецької, а відтак, гірші показники грамотності рідної мови.
Турецькі діти в Німеччині, які вивчають граматичні категорії турецької мови як рідної
Keywords: Turkish; mother tongue; bilingualism; турецька мова; рідна мова; двомовність